2022
DOI: 10.1155/2022/7751263
|View full text |Cite|
|
Sign up to set email alerts
|

Review on Epileptic Seizure Prediction: Machine Learning and Deep Learning Approaches

Abstract: Epileptic seizures occur due to brain abnormalities that can indirectly affect patient’s health. It occurs abruptly without any symptoms and thus increases the mortality rate of humans. Almost 1% of world’s population suffers from epileptic seizures. Prediction of seizures before the beginning of onset is beneficial for preventing seizures by medication. Nowadays, modern computational tools, machine learning, and deep learning methods have been used to predict seizures using EEG. However, EEG signals may get c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 62 publications
(59 reference statements)
0
15
0
Order By: Relevance
“…It is partly because of their ensemble nature and multiple logic rules [127]. ey can achieve fairly good classification results as shown in the previous sections [134][135][136][137][138][139][140][141][142]. Decision tree-based models can handle a relatively large number of datasets and are less time-consuming and mostly yield high accuracy, precision, and recall.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is partly because of their ensemble nature and multiple logic rules [127]. ey can achieve fairly good classification results as shown in the previous sections [134][135][136][137][138][139][140][141][142]. Decision tree-based models can handle a relatively large number of datasets and are less time-consuming and mostly yield high accuracy, precision, and recall.…”
Section: Discussionmentioning
confidence: 98%
“…(c) Because a large amount of dataset is required for the proper validation of a machine learning model for epileptic seizure detection and classification, plenty of efforts have been made to combine available EEG datasets for this purpose. However, it is still difficult to combine these datasets because they have different parameters and were acquired under relatively different sampling conditions [142]. (d) Because machine/deep learning models mostly require substantial computational resources for their implementation in practical settings, which are sometimes difficult to access, a piece of good knowledge about how to optimize the models' performance is necessary for realizing a practical epileptic seizure detection and classification system.…”
Section: Observed Challenges From Surveyed Literaturementioning
confidence: 99%
“…Machine learning algorithms can analyze records containing a large number of variables and can find complex linear or non-linear relationships between variables ( Gazda et al, 2021 ). Machine learning and deep learning methods have been used to analyze EEG to predict various chronic psychiatric illnesses ( Natu et al, 2022 ; Paul et al, 2022 ). Using artificial intelligence and machine learning to comprehensively analyze MRI and EEG to diagnose HE more accurately may be the direction of future research.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Nair et al [ 85 ] concluded that the AI-based approaches have been tremendously contributed to epilepsy detection, prediction, and management for an improved healthcare society. Likewise, Natu et al [ 86 ] presented a wholistic view of AI and ML applications in epilepsy detection. It encompasses, data preprocessing approaches, channel selection methods followed by the classifier or the prediction model.…”
Section: Literature Reviewmentioning
confidence: 99%